Peran Orang Tua Dalam Membimbing Anak Belajar Dari Rumah di Kelas IVb SDN Pakuhaji - Sinta Suryani; Rusi Rusmiati Aliyyah; Iyon Muhdiyati (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This study aims to determine the role of parents in guiding children to learn from home at the Pakuhaji Parungkuda Public Elementary School (SDN). This research is a type of qualitative research with a case study method. Data collection techniques using observation, interviews, documentation and questionnaires. The data analysis procedure uses Miles and Huberman, through data reduction, data presentation, and drawing conclusions. Check the validity of the data using triangulation of sources and techniques. The respondents of this study were fourth grade teachers, parents and students. The results showed that parents prepared learning tools (tools) for children including cellphones, books, study tables and provided comfortable places for children such as in the room, in the tv room and in the terrace. Parents help children overcome learning difficulties, namely by helping explain material that they do not understand in learning and providing examples in working on the questions given by the teacher. The inhibiting factors faced by parents during learning from home are due to 1) the availability of parental time is inadequate in supervising children during learning such as dividing time by selling and taking care of the household by doing homework, 2) low economic conditions in meeting children's learning needs including quotas must always be available to facilitate learning and prepare cellphones to be able to take part in learning.